PENINGKATAN JUMLAH NASABAH PADA PT. BRI (PERSERO), TBK CABANG MAKASSAR MELALUI STRATEGI PROMOSI - Hasriani Hasriani (AkMen JURNAL ILMIAH, 2009)
PT. Bank of Indonesia People, Tbk as one of industrial perpetrator of banking in Indonesia also run the promotion strategy program Let to Bank from Indonesia Bank. The Program be of benefit to party PT. BRI, TBK Branch the Makassar to increase sum up its client. PT. BRI, Tbk Branch the Makassar try to add its client therewith its deposit through promotion activity. More and more a lot of client hence more and more a lot of unrightious fund [of] k three which can be obtained. Promotion strategy let to BANK have been applied by PT. BRI, Tbk Branch the Makassar better. In its execution hence multifarious promotion strategy of information take possession of the first sequence, later then partake the deposit and invesment, credit card, credit and flower recognition and last of complain. Since year 2006 until year 2007 client amount experience of the improvement which signifikan. Client interested to save money in the form of deposit of kemuadian of giro and saving